Effect of Family Hope Program on Maternal Health Behavior and Children Under Five Nutritional Status in Poor Families, Jombang, East Java - Rosalina, Sintya; Sulaeman, Endang Sutisna; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Family Hope Program, or internationally referred to as Conditional Cash Transfer (CCT), is a government poverty allevation initiative by provision of conditional cash money that induces healthy behavior so as to achieve strong generation. This study sought to examine the effect of Family Hope Program on maternal health behavior and children under five nutritional status in poor families, Jombang, East Java. Subjects and Method: This was an analytic observational study with retrospective cohort design. This study was conducted in Jombang District, East Java, from November to December 2017. A total sample of 210 mothers and their children under five were selected for this study by fixed exposure sampling. The dependent variables were maternal health behavior and child nutritional status. The independent variables were birthweight, history of illness, maternal education, family income, family support, government Family Hope Program,